지적측량 적부심사 유형별 사례분석에 관한 연구 - 오이균; OH, Yi-Kyun (지적과 국토정보, 2022)
The cadastral boundary points which cadastral surveyor presented on the ground by conducting cadastral surveying represents the limits of land ownership and give binding force and determination power. However the land disputes have increased these days mainly due to cadastral registration errors, surveying errors and land owners recognition error. In these cases, the cadastral survey interests try to find solution by either a administrative procedures by appealing civil complaint or border determination litigation through court. The neighboring residents and related organization have difficulties in resolving the civil complaints. In this study cadastral surveying and cadastral boundary determination process has been reviewed and the results of cadastral surveying screening by Central Cadastre Committee from 2016 to 2021 have been classified. The outcomes of this research will be used for cadastral surveying and contribute for reducing land disputes and improve reliablity of cadastral surveying. 지적측량사가 지적경계복원측량을 통하여 지상에 표시한 경계는 소유자의 소유권의 한계를 명확히 밝힌 것으로 구속력과 확정력을 갖게 된다. 그러나 등록상의 오류라든지 측량상의 문제, 소유자의 경계점 인식 오류 등 제반 요인들로 인하여 매년 지적측량 분쟁에 따른 민원이 끊이지 않고 발생하고 있다. 지적측량 이해당사자들은 지적측량의 이의를 해결하기 위하여 먼저 민원제기에 따른 행정적 절차를 통한 해결 방법과 법원을 통한 경계확정소송을 통한 해결방안을 모색하게 된다. 그 결과 경계에 인접한 이해 당사자 들은 물론 관련 공적 기관들에 있어 민원 해결을 위한 어려움들이 발생하게 된다. 따라서 본 연구에서는 지적측량과 경계결정에 대한 사항을 고찰하고, 2016년부터 2021년까지 6년여 동안 중앙지적위원회에서 심의 의결한 지적측량적부재심사 사례를 유형별로 분류하고 그 대표적 사례들을 분석 제시함으로써 추후 지적측량을 실시함에 있어서 이들 사례를 참고하여 경계분쟁 사례를 줄이고 지적측량의 신뢰성 향상에 기여하고자 한다.